Fresno County Bar Association Luncheon with St. Bar President Colin Wied Speaking on Redistricting - Watkins, Howard::::::::: (1989)
President Wied noting that Riverside and San Bernardino Counties may be added to Central Valley's district In rebuttal, District 5 Governor Robert Oliver spoke against the proposal